Motor skills building process profiling study - Goncharov, V. I.; Mukhachev, E. A. (Theory and Practice of Physical Culture, 2017)
The article considers benefits of the express-method designed by the authors to profile the motor skills building process. The method is based on a software that gives the means to fix and analyse the process data by the test that requires specific words being typed using a computer keyboard. The specific word-processing and typing tasks were designed to help master certain movement sequences that cover every component of the motor skill building process i.e. central, vegetative and peripheral components. The test data analyses produced the data arrays that may be interpreted in many aspects of the motor skills building process related matters, albeit the study was limited by the CYSS trainees only. Objective of the study was to obtain the motor skills building process profiles for the single-phase and multiphase skill-mastering sessions. The motor skills building process data profiles were classified on a success-specific basis, i.e. for highly- and low-successful trainees, with an emphasis on the skill succession processes applied in a sequence of sessions including the reminiscence (memorizing) mechanism application.